2018
DOI: 10.3390/su10051509
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Communication in an Online Q&A Community: A Case Study of Quora

Abstract: An emerging research trend in climate change studies is to use user-generated-data collected from social media to investigate the public opinion and science communication of climate change issues. This study collected data from the social Q&A website Quora to explore the key factors influencing the public preferences in climate change knowledge and opinions. Using web crawler, topic modeling, and count data regression modeling, this study quantitatively analyzed the effects of an answer's textual and auxiliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Big data analyses have indicated that when interpreting climate events, individuals' preference for frameworks was influenced by demographics [5] and social-political background [2]. Different choices of frameworks can evoke different psychological processes [30], promote or inhibit engagement intentions [31], or gain approval on various levels [32].…”
Section: Climate Change Global Warming and Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Big data analyses have indicated that when interpreting climate events, individuals' preference for frameworks was influenced by demographics [5] and social-political background [2]. Different choices of frameworks can evoke different psychological processes [30], promote or inhibit engagement intentions [31], or gain approval on various levels [32].…”
Section: Climate Change Global Warming and Framesmentioning
confidence: 99%
“…There are many other words in tweets besides hashtags to express the author's intention. Multiple approaches, such as LDA and STM [32,73], can help to extract topics from unstructured texts. But in this study, targeting on hashtags is more in line with our research question.…”
Section: Hashtags As Frame Vehicles On Social Mediamentioning
confidence: 99%
“…However, the question-and-answer systems used to solve assignments for a particular course are very rare. As a result, an intelligent question-and-answer system has been developed that returns answers to users' questions according to the principles of a course based course [3] [19]. In this article, we introduce how open vocabulary fits in natural language processing along with machine learning can be used to infer a person's personality from their language use in a hiring interview.…”
Section: Related Workmentioning
confidence: 99%
“…However, blog owners that deny or downplay global warming attempted to disregard the overwhelming scientific evidence, such as Arctic sea‐ice loss and polar bear vulnerability, to cast doubt on other established ecological consequences of global warming, thereby aggravating the consensus gap (Harvey et al , ). A case study on the question–answer community Quora also suggests that emphasis on specific subjects but not popular knowledge of climate change could draw more public attention on the issue of climate change (Jiang et al , ). Brandt et al .…”
Section: Review Of Previous Work and Analysismentioning
confidence: 99%